2020
DOI: 10.1186/s12879-020-04987-8
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity, vulnerability and mistrust: how context, information and government affect the lives of women in times of Zika

Abstract: Background: The public health response to Zika outbreak has mostly focused on epidemiological surveillance, vector control, and individual level preventative measures. This qualitative study employs a social-ecological framework to examine how macro (historical, legislative, political, socio-economic factors), meso (sources of information, social support, social mobilization) and micro level factors (individual actions, behavioral changes) interacted to influence the response and behavior of women with respect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
4
15
0
1
Order By: Relevance
“…We found similarities between our study and a recently published article by Linde-Arias et al [ 16 ]. Knowledge levels about ZIKV highly depend on news, access to health services and the kind of relationship with healthcare professionals; similarly, knowledge translates into perceptions that can crucially shape attitudes and practices towards preventive measures, healthcare-seeking behavior and reproductive decisions.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found similarities between our study and a recently published article by Linde-Arias et al [ 16 ]. Knowledge levels about ZIKV highly depend on news, access to health services and the kind of relationship with healthcare professionals; similarly, knowledge translates into perceptions that can crucially shape attitudes and practices towards preventive measures, healthcare-seeking behavior and reproductive decisions.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding their emotional status, we reported different feelings captured during the interviews; sadness, responsibility, shame, guilt, stigma, loneliness, sorority/sisterhood and empathy, as well as psychological suffering, anxiety and depression. Same feelings and emotions, many of them reflecting poor mental health, were reported in other studies [ 16 , 39 , 40 ]. In our study, women declared that their partners and relatives were their main source of support during pregnancy to cope with uncertainties about ZIKV, the possible transmission of infection to the fetus and repercussions on children’s health.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…They also concluded that lack of trust in governments made women more vulnerable because they did not completely follow the health authorities' instructions. This example indicates the role of political and social context in the success of a PHI [ 30 ]. Effectiveness of a non-pharmaceutical PHI is tailored to changing the behavior of the target population [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%